I.T. Skills Accountants: A Study on Job Ads - Sari, Lidya Puspita; Suryani, Ani; Yusoff, Zetty Zahureen Mohd (Accounting Department, 2022)
Purpose—This study aims to identify the IT skills required for accounting staff, managers, and supervisor positions in the labour market and assist prospective accounting graduates in building the necessary skills to obtain the desired career. Design/methodology/approach—This study utilized the content analysis method to analyze 543 job advertisements from the Job Street website. The data was then tested using the Kruskal-Wallis test to determine the differences in the skill requirements between positions. Findings — The skills most in demand across all positions are those associated with Microsoft Office and accounting software. The difference in needs at staff, supervisor, and manager positions was confirmed. Practical implications — This study informs prospective accounting graduates about the labour market’s skill requirements. It is expected to raise graduates’ awareness and understanding, allowing them to prepare the skills required for the expected jobs. Originality/value—This study contributes to the previous literature by identifying the intensity of the need for information technology skills in the current digital era through the percentage of needs. Framed in the signalling theory, the content analysis of the paper presents a comparison of skills required among different positions (staff, supervisor, manager). Keywords — accountant; content analysis; IT skills; job advertisement; data analytic; accounting software Paper type — empirical paper